PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS GOOGLE SITE DALAM MENINGKATKAN EFEKTIVITAS BELAJAR PADA MATA PELAJARAN TEKNIK GAMBAR PRODUKSI - Ramdhan Wijdan Denawan, - (2023)
This research is aimed at producing a product of digital teaching materials based on Google Site for the subjects of image production engineering topic in SMK Negeri 2 Kota Bandung which can be used to support the learning process throughout the day to help teachers in matching the teaching material. The research was carried out at SMK Negeri 2 Kota Bandung with expertise in Engineering Design and Machine Imaging. This research method uses the Design Based Research method with data collection techniques using a lift. The results of this study showed that the media is worthy of use based on the Judgement test by the experts obtained a 95% score on the material with the criterion "Very Worthy" and on the media obtaining a score of 84% with the "very Worth" criterions as well as the media received a response from either the user or the student participant proved with a user response score of 79.9% on the "Good" criteria.